The burden of modernity : the rhetoric of cultural discourse in Spanish America - Alonso, Carlos J. (Oxford University Press, 1998)
An interpretation of cultural discourse in Spanish America which argues that Spanish American cultural production is marked by an internal rhetoric crisis that resulted from the adoption of discourses regarded as modern in historical and economic circumstances that are, in fact, the negation of modernity.
Keywords: Spanish American prose literature -- 19th century -- History and criticism.; Spanish American prose literature -- 20th century -- History and criticism.; Narration (Rhetoric); Latin America -- Intellectual life -- 19th century.; Latin America -- Intellectual life -- 20th century.; Prose hispano-américaine -- 19e siècle -- Histoire et critique.; Prose hispano-américaine -- 20e siècle -- Histoire et critique.; Narration.; Amérique latine -- Vie intellectuelle -- 19e siècle.; Amérique latine -- Vie intellectuelle -- 20e siècle.; LITERARY CRITICISM -- European -- Spanish & Portuguese.; Intellectual life; Spanish American prose literature; Latin America; Spaans.; Proza.; 1800-1999; Criticism, interpretation, etc.